The Effect of Non-pooled Multidonor Faecal Microbiota Transplantation for Inducing Clinical Remission in Patients with Chronic Pouchitis: Results from a Multicentre, Randomised, Double-blinded, Placebo-controlled Trial [MicroPouch] - Kousgaard, Sabrina Just; Cold, Frederik; Halkjær, Sofie Ingdam; Petersen, Andreas Munk; Kjeldsen, Jens; Hansen, Jane Møller; Dall, Sebastian Mølvang; Albertsen, Mads; Nielsen, Hans Linde; Kirk, Karina Frahm; Duch, Kirsten; Sønderkær, Mads; et al. (Journal of Crohn's and colitis, 2024)
Abstract Background and Aims To investigate if treatment with non-pooled, multidonor faecal microbiota transplantation [FMT] for 4 weeks was superior to placebo to induce clinical remission in patients with chronic pouchitis. Methods The study was a randomised, double-blinded, placebo-controlled study with a 4-week intervention period and 12-month follow-up. Eligible patients with chronic pouchitis were recruited from five Danish hospitals. Participants were randomised to non-pooled, multidonor FMT derived from four faecal donors, or placebo. Treatment was delivered daily by enema for 2 weeks, followed by every second day for 2 weeks. Disease severity was accessed at inclusion and 30-day follow-up, using the Pouchitis Disease Activity Index [PDAI]; PDAI <7 was considered equivalent to clinical remission. Faecal samples from participants and donors were analysed by shotgun metagenomic sequencing. Results Inclusion was stopped after inclusion of 30 participants who were randomised 1:1 for treatment with FMT or placebo. There was no difference in participants achieving clinical remission between the two groups at 30-day follow-up, relative risk 1.0 (95% CI [0.55; 1.81]). Treatment with FMT resulted in a clinically relevant increase in adverse events compared with placebo, incidence rate ratio 1.67 (95% CI [1.10; 2.52]); no serious adverse events within either group. Faecal microbiota transplantation statistically significantly increased the similarity of participant faecal microbiome to the faecal donor microbiome at 30-day follow-up [p = 0.01], which was not seen after placebo. Conclusions Non-pooled, multidonor FMT was comparable to placebo in inducing clinical remission in patients with chronic pouchitis, but showed a clinically relevant increase in adverse events compared with placebo. ClincialTrials.gov number, NCT04100291. Graphical abstract Graphical Abstract